Pedagogical communication – achievement and frequency in general class teaching - Panić, Danijela S; Lazić, Dragana D; Mitrović, Ljiljana LJ (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
This paper deals with pedagoical cmmunications, that is, the frequency and achievement of communication in general class teaching. The aim of this research is definition of frequency and achievement of pedagogical communication, regarding the communication direction (pupil-teacher, teacher-pupil and pupil-pupil). Also, the aim of this research is to define the frequency and successfulness during teaching of subjects group (common - educational and skills) and to define the communication relation regarding to the type, that is, group which teaching subject belongs to. The nature of problem and set aim of research determined that this research has an empirical character. From the set aim and objective of this research, the following research tasks are derived: to establish the incidence and successfulness of pedagogical communication towards teaching subjects in general class teaching on relations teacher-pupil, pupil-teacher, pupil-pupil, over 300 lessons; to establish whether there is statistically significant difference in communication  achievement and unachievement towards teaching subjects on relations, in general class teaching; to establish whether there is statistically significant difference in the communication incidence and achievement between common educational group of teaching subjects and skills. The research was conducted by method of observing, noting and specially designed instrument for this kind of data and research was used. The results shows that the communication is the most incident and most achieved on relation teacher – pupil, as well as that achievement and unachievement of communications depends on the type of teaching subject. Since the pedagogical communication is very important part in pedagogical and educational work in our schools, this paper offers useful information for further studies, improvement of communication in teaching.
Keywords: elementary school; achievement; teaching subject; class teaching; pedagogical communication